Globalisation, ICT Investment and Firm Dynamism. Issue 2 (2nd April 2020) - Tang, Jianmin; Wang, Weimin; Yu, Zhihao
Abstract: There have been strong evidence showing a declining trend of firm dynamism in many other OECD countries over the last three decades. However, so far there has no compelling evidence that points to any intrinsic factor(s) that may have affected the trend of declining firm dynamism. This paper investigates some potential candidates for the intrinsic factors that might be responsible for the decline in firm dynamism. Specifically, it hypothesises that globalisation and ICT (information and communication technology) have increased the flexibility in business operation, which has contributed to the decline in firm dynamics because firms can better weather positive/negative shocks with increasing business flexibility. Using data from Canada, we find empirical support for the linkage between business flexibility and firm dynamics in Canada.